Insecticide Residuality of Mexican Populations Occupationally Exposed - Aldana-Madrid, María-Lourdes; Silveira-Gramont, María-Isabel; Zuno-Floriano, Fabiola-Gabriela; Rodríguez-Olibarría, Guillermo (IntechOpen, 2013)
None